The nature and organization of satellite DNAs in Petunia hybrida, related, and ancestral genomes - Alisawi, Osamah; Richert-Pöggeler, Katja R.; Heslop-Harrison, J.S. (Pat); Schwarzacher, Trude (Frontiers in Plant Science, 2023)
The garden petunia, Petunia hybrida (Solanaceae) is a fertile, diploid, annual hybrid species (2n=14) originating from P. axillaris and P. inflata about 200 years ago. In order to understand the recent evolution of the P. hybrida genome in more detail, we examined tandemly repeated or satellite DNA sequences using bioinformatic analysis of raw reads from available genomic assemblies and survey sequences of P. axillaris N (PaxiN), P. inflata S6, (PinfS6), P. hybrida (PhybR27) and the here sequenced P. parodii S7 (PparS7). Graph and k-mer based cluster analysis using TAREAN and RepeatExplorer displayed varied ring-shaped graphs and identified repeat specific monomer lengths of the major tandem repeat families with more than 0.01% genome proportion. Seven distinct repeat families, PSAT1, PSAT3, PSAT4, PSAT5, PSAT6, PSAT7 and PSAT8, each shared sequence similarity and organisation between the four genomes. Additionally, many degenerate copies of each were present. Fluorescent in situ hybridization in P. hybrida (W138, V26 and RdC) and in the three wild petunias confirmed the bioinformatics data and gave corresponding signals on all or some chromosomes. Repeat PSAT1 is located at the ends of all chromosomes except the 45S rDNA bearing short arms of chromosomes II and III, and we classify it as a telomere associated sequence (TAS). It is the most abundant satellite repeat with over 300,000 copies, representing 0.2% of the genomes. PSAT3 and the variant PSAT7 are located adjacent to the centromere or mid-arm of one to three chromosome pairs. PSAT5 has a strong signal at the end of the short arm of chromosome III in P. axillaris and P.inflata, while in P. hybrida additional interstitial sites were present. PSAT6 is located at the centromeres of chromosomes II and III. PSAT4 and PSAT8 were found with only short arrays. These results demonstrate that (i) repeat families occupy distinct niches within chromosomes, (ii) they differ in the copy number, cluster organization and homogenization events, and that (iii) the recent genome hybridization in breeding P. hybrida preserved the chromosomal position of repeats but affected the copy number of repetitive DNA.